2021
DOI: 10.3390/polym13203475
|View full text |Cite
|
Sign up to set email alerts
|

The Crystallisation, Microphase Separation and Mechanical Properties of the Mixture of Ether-Based TPU with Different Ester-Based TPUs

Abstract: The difference in compatibility at the molecular level can lead to a change of microphase separation structure of thermoplastic polyurethanes blend systems, which will improve their thermal and mechanical properties. In this study, TDI-polyester based TPU was blended with MDI-polyether-based TPU and MDI-polyester based TPU, with different ratios. In the blend system, the obvious reduction of the melting temperature of the high-temperature TDI-polyester based TPU component indicates its hard segments can be mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Gel permeation chromatography (GPC) experiments reported in previous studies had indicated high molecular weights ( M w >150 000 Da) and broad molecular weight distributions ( M w / M n > 2.0) for the TPUs [ 53 ] and thermoplastic styrene–butadiene copolymers [ 54,55 ] examined. These materials exhibited low glass transition temperatures, in keeping with their elastomeric properties.…”
Section: Methodsmentioning
confidence: 99%
“…Gel permeation chromatography (GPC) experiments reported in previous studies had indicated high molecular weights ( M w >150 000 Da) and broad molecular weight distributions ( M w / M n > 2.0) for the TPUs [ 53 ] and thermoplastic styrene–butadiene copolymers [ 54,55 ] examined. These materials exhibited low glass transition temperatures, in keeping with their elastomeric properties.…”
Section: Methodsmentioning
confidence: 99%
“…For PBA-based TPUs the crystallization kinetics and crystal phase composition was analyzed as a result of competition between the nucleation and crystal phase growth, from one side, and phase separation efficiency above the melting point of PBA and linear, aromatic and cycloaliphatic urethane blocks, from the other side. In general, for TPU the phase separation of hard and soft blocks that governs the final morphology, mechanical and thermal properties [ 12 , 13 ]. The incompatibility between the blocks can be finetuned not only by changing the composition and ratio of soft and hard segments but also by variation of hydrogen bonding caused by addition of nanofillers or by use of specific thermal programs [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The structure of soft segments is defined by oligodiols used for SPU synthesis [ 8 ]. Hard segments are formed by the reaction of isocyanate terminated compounds, oligodiisocyanates, with low molecular weight chain extenders diamines or diols [ 9 ].…”
Section: Introductionmentioning
confidence: 99%